Impact of Chronic Kidney Disease on Short-Term Cardiac Implantable Electronic Device Related Infection: A Nationwide Population-Based Cohort Study. Issue 5 (February 2016) - Lin, Yu-Sheng; Chen, Tien-Hsing; Lin, Ming-Shyan; Chen, Dong Yi; Mao, Chun-Tai; Hsu, Jen-Te; Chen, Huang-Chung; Chen, Mien-Cheng
Abstract : Abstract: Chronic kidney disease (CKD) increased the incident cardiac implantable electronic device (CIED) infection, but risk factors of CIED infection in CKD patients remain unclear. Patients who received new CIED implantation between January 1, 1997 and December 31, 2011 were selected from the Taiwan National Health Insurance Database and were divided into 3 groups: patients with normal renal function, CKD patients without dialysis, and CKD patient with dialysis. Two outcomes, CIED infection during index hospitalization and within 1 year after discharge, were evaluated. This study included 38, 354 patients, 35, 060 patients in normal renal function group, 1927 patients in CKD without dialysis group, and 1367 patients in CKD with dialysis group. CKD patients without dialysis (adjusted odds ratio [aOR], 2.14, 95% confidence interval [CI], 1.32-3.46) and CKD patients with dialysis (aOR, 3.78, 95% CI, 2.37-6.02) increased incident CIED infection during index hospitalization compared to patients with normal renal function. Use of steroid (aOR: 2.74, 95% CI, 1.08-6.98) increased the risk of CIED infection in CKD patients without dialysis while chronic obstructive pulmonary disease (COPD) (aOR: 2.76, 95% CI, 1.06-7.16) increased the risk of CIED infection in CKD patient with dialysis during index hospitalization. CKD is a risk of CIED infection during index hospitalization. Use of steroid and COPD are important risks factors for CIED infection in CKD patients. Abstract : Supplemental Digital Content is available in the text